Development of peptide inhibitors of HIV transmission - Siyu Shi; Peter K. Nguyen; Henry J. Cabral; Ramon Diez-Barroso; Paul J. Derry; Satoko M. Kanahara; Vivek A. Kumar (Bioactive Materials, 2016)
Treatment of HIV has long faced the challenge of high mutation rates leading to rapid development of resistance, with ongoing need to develop new methods to effectively fight the infection. Traditionally, early HIV medications were designed to inhibit RNA replication and protein production through small molecular drugs. Peptide based therapeutics are a versatile, promising field in HIV therapy, which continues to develop as we expand our understanding of key protein-protein interactions that occur in HIV replication and infection. This review begins with an introduction to HIV, followed by the biological basis of disease, current clinical management of the disease, therapeutics on the market, and finally potential avenues for improved drug development.